2017
DOI: 10.5530/ijper.51.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Anticancer Activity of 1, 3, 4-Oxadiazole Derivatives against Ehrlich Ascites Carcinoma Bearing Mice and Their Correlation with Histopathology of Liver

Abstract: A series of 2, 5-disubstituted 1, 3, 4-Oxadiazole derivatives (4A-4G) have been synthesized with the help of different aromatic benzaldehyde and final compounds were characterized by FT-IR, 1 H NMR and Mass spectroscopy. The anticancer study was investigated against Ehrlich Ascites Carcinoma (EAC) bearing albino mice. The synthesized (4A-4G) compounds were administered intraperitoneally at dose of 20-25 mg/kg; body weight per day for 7 days after 24 hour of tumor inoculation in mice. The standard compound used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Moreover, CHK9 did not exhibit toxicity up to 20 mg/kg body weight in the tested animals. 1,3,4-oxadiazoles have displayed similar toxicity profiles in the previous in vitro and in vivo studies [ 55 , 56 ]. A limited number of studies have demonstrated the in vivo antitumor activity of oxadiazoles.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, CHK9 did not exhibit toxicity up to 20 mg/kg body weight in the tested animals. 1,3,4-oxadiazoles have displayed similar toxicity profiles in the previous in vitro and in vivo studies [ 55 , 56 ]. A limited number of studies have demonstrated the in vivo antitumor activity of oxadiazoles.…”
Section: Discussionmentioning
confidence: 60%
“…A Monte Carlo Simulations studies suggested that the schiff bases containing the >C=N group possessed antitumor activity (Guimaráes et al, 2005). In this context, Roy et al (2017) designed and reported 1,3,4-oxadiazole containing >C=N group at its 2 position. The researchers synthesized new 2,5-disubstituted-1,3,4-oxadiazole derivatives and studied their anticancer activity and histopathological study of the liver was performed.…”
Section: Linked-134-oxadiazolesmentioning
confidence: 99%
“…The fluorescence properties of all the compounds were analysed in dimethyl sulfoxide media and were evaluated for their n vitro inhibitory activity against commercial enzyme xanthine oxidase (XO) by measuring the formation of uric acid from xanthine. [17] (2017) were synthesised some novel 2, 5-Disubstituted 1, 3, 4-Oxadiazole derivatives (scheme: 20) using different aromatic benzaldehyde, and evaluated for their anticancer activity against Ehrlich Ascites Carcinoma (EAC) bearing albino mice. …”
Section: Ar= Aryl Halidesmentioning
confidence: 99%